2010
DOI: 10.1002/nme.3083
|View full text |Cite
|
Sign up to set email alerts
|

Confidence structural robust optimization by non‐linear semidefinite programming‐based single‐level formulation

Abstract: SUMMARYStructural robust optimization problems are often solved via the so-called Bi-level approach. This solution procedure often involves large computational efforts and sometimes its convergence properties are not so good because of the non-smooth nature of the Bi-level formulation. Another problem associated with the traditional Bi-level approach is that the confidence of the robustness of the obtained solutions cannot be fully assured at least theoretically. In the present paper, confidence single-level n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…With the relations in Equations (17) and (19) in mind, by applying the lemmas in convex analysis (see the Appendix for details) as in other works, 13,[21][22][23][24] it can be concluded that the sensitivity u l / a i is bounded in terms of…”
Section: Interval Methods For Sensitivity Boundingmentioning
confidence: 94%
See 1 more Smart Citation
“…With the relations in Equations (17) and (19) in mind, by applying the lemmas in convex analysis (see the Appendix for details) as in other works, 13,[21][22][23][24] it can be concluded that the sensitivity u l / a i is bounded in terms of…”
Section: Interval Methods For Sensitivity Boundingmentioning
confidence: 94%
“…Table 6 presents the calculated lower and upper sensitivity bounds of u 13y / A i (i = 1, … , 51) with use of the proposed iterative interval sensitivity bounding method. It can be found that, among totally 51 binary discrete variables, the optimal values of 18 0-1 variables (x i , i ∈ I 1 = {5, 9,10,14,15,17,19,22,24,27,28,32,33,38,40,43,45, 50}) can be determined directly in the first-round sensitivity bounding analysis. With these obtained values being fixed another 15 values of x i , i ∈ I 2 = {1, 4,12,13,18,20,23,26,29,34,35,37, 39, 48, 51} can be found from monotonic analysis in the second-round sensitivity bounding process.…”
Section: A 51-bar Truss Arch Bridgementioning
confidence: 99%
“…In the following, we add (24) to problem (23). It is worth noting that a truss design involving a chain is infeasible for the presented robust optimization problem, because it is unstable and cannot be in equilibrium with uncertain forces applied to an intermediate node of the chain.…”
Section: Treatment Of Members Lying On a Linementioning
confidence: 99%
“…By relaxing the 0-1 constraints into linear inequality constraints, we obtain an SDP relaxation. Since SDP can be solved efficiently with a primal-dual interior-point method, we can find a global optimal solution of problem (23) with a branch-and-bound method [59].…”
Section: Review Of Existing Formulationmentioning
confidence: 99%
See 1 more Smart Citation